The relationship between nurse leadership and emotional intelligence: a literature review - Lipickytė, Erika; Sabaliauskas, Stanislav; Klyčmuradov, Murad (Slauga. Mokslas ir praktika, 2023)
Today’s healthcare system needs people who can work independently, be proactive, make responsible decisions and deliver effective results. Nurses with higher emotional intelligence are more likely to be more communicative and empathetic, which contributes significantly to a good relationship with the patient and to good performance. Leadership qualities are not only present in the nurse administrator in a managerial position, but also in the nurse who interacts with patients on a daily basis. The relationship between nurses’ emotional intelligence and leadership is an area of research that is relatively new. Aim of the study. To investigate the relationship between emotional intelligence and leadership in nursing by analysing the results of existing research. Methods. A literature search was conducted in the PubMed database. According to the exclusion and inclusion criteria, 5 scientific articles were included and analysed in the systematic review. Results and conclusions. The results of the study revealed the main issues raised in the scientific literature - the strengthening of nurses’ leadership, the development of emotional intelligence and leadership, and the impact of team leader’s emotional intelligence on the stress experienced by nurses. The literature analysis also reveals that leaders with emotional intelligence, both in managerial and non-managerial roles, lead to higher quality nursing outcomes and improvements in other factors such as effective communication, and that the development of nurses’ leadership and emotional intelligence in undergraduate study programmes requires the introduction of a dedicated course.